The rule of law in criminal justice - Lamarca Pérez, Carmen (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The author studies the political meaning and the juridical requirements coming from the principle of penal legality in force. First, it is analyzed the content of the principle of juridical security, from which results at the same time the requirements of “lex certa” and “lex praevia” and the democratic-representative principle or the principle of reserve of law, which demands that the law should be written and would state the prohibition of the analogy. It is examined, at the second place, the factors which from the last century are contributing to what is known at work as the decline of the law. Finally, the exam of the concept is completed with a critical analysis of the regulation of the principle of penal legality within Spain, paying special attention to the constitutional jurisprudence on the matter.
Keywords: Legal security; strict character of the penal norm; law reserve; law empire; law decline